2016
DOI: 10.1161/strokeaha.115.011291
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cortical Vein Thrombosis

Abstract: Background and Purpose Cortical vein thrombosis (CVT) is an uncommon site of involvement in cerebral sinovenous thrombosis (CSVT). Few reports have described pediatric CVT, and none have differentiated its unique attributes. This study assessed the clinical features and radiographic outcome of a cohort of children with CSVT, comparing those with CVT to those without CVT. Methods Children diagnosed with CSVT were retrospectively reviewed and separated into two groups based on the presence or absence of cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 7 publications
2
5
1
2
Order By: Relevance
“…In our study, a higher incidence (61.4%) of concomitant CVT was found among adult CVST patients than pediatric CVST patients (24%) and the rate reported in a previous study (17%) [ 3 , 6 ], which might be due to the integration of multiple imaging techniques for the detection of CVTs in our study (see Additional file 1 : Tables S1 and S2).…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…In our study, a higher incidence (61.4%) of concomitant CVT was found among adult CVST patients than pediatric CVST patients (24%) and the rate reported in a previous study (17%) [ 3 , 6 ], which might be due to the integration of multiple imaging techniques for the detection of CVTs in our study (see Additional file 1 : Tables S1 and S2).…”
Section: Discussionsupporting
confidence: 48%
“…With the development of non-invasive neuroimaging techniques (e.g., magnetic resonance imaging [MRI] and computed tomography [CT]) and improved recognition of CVT, a greater incidence of CVT has been diagnosed with contemporary neuroimaging techniques compared to the past decade. In a recent study that included pediatric CVST patients [ 6 ], concomitant CVT was found to be not rare (24%) and was associated with seizures and brain lesions. However, the significance of concomitant CVT in adult CVST patients is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are partially consistent with those of previous researchers, but there are some discrepancies (5,13). According to their studies, seizure, FND, altered consciousness, venous infarction, ICH, SAH, and concurrent SSS thrombosis were more frequent in the CVI group than in the CVI negative group (5,13) and the mRS score at discharge was higher for the CVI group than the CVI-negative group (5). Although we cannot accurately explain why our results differ from those of other researchers, it might be caused by differences in the patient population.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the CVI of CVT in our patients, the CVI was demonstrated in 31 patients (63.3%) and the CV was the most common site of CVT, which is higher than those of previous studies (2,9,10,13). They reported 3.4% -23% incidence of CVI.…”
Section: Discussioncontrasting
confidence: 64%
“…Traditionally, cortical vein thrombosis has been thought to be rare. However, a recent study of cortical vein thrombosis in children reported that almost a quarter of the patients with CSVT actually had cortical vein thrombosis; the children with cortical vein thrombosis also were more likely to have significant neurological complications, such as infarction and seizures [ 5 ].…”
mentioning
confidence: 99%